1998
DOI: 10.1046/j.1360-0443.1998.9333373.x
|View full text |Cite
|
Sign up to set email alerts
|

A short questionnaire (IRQ) to assess injecting risk behaviour

Abstract: IRQ performs well in a variety of settings, when administered in different ways to different kinds of IDUs. A single question on 'sharing' elicits fewer positive responses than the use of multiple questions about different sharing practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 6 publications
0
23
0
2
Order By: Relevance
“…Participants were also asked whether they shared other injection equipment, such as mixing containers, cookers, water, etc., during the episode. This, however, is a separate behavior, less reliably recalled (Stimson et al 1998) and not the focus of the present study.…”
Section: Methodsmentioning
confidence: 70%
“…Participants were also asked whether they shared other injection equipment, such as mixing containers, cookers, water, etc., during the episode. This, however, is a separate behavior, less reliably recalled (Stimson et al 1998) and not the focus of the present study.…”
Section: Methodsmentioning
confidence: 70%
“…32 A validade de construção ("construct validity") foi avaliada pela utilização da análise de componentes principais, e a validade colateral ("collateral validity") foi inferida da correlação do instrumento com outro questionário independentemente aplicado. Com nosso instrumento, um possível caminho para avaliar a validade seria medi-la separadamente para cada seção do instrumento.…”
Section: Discussionunclassified
“…The sharing of injecting equipment in the four weeks prior to interview was investigated over a set of seven questions, adapted from the Injecting Risk Questionnaire (Stimson et al, 1997). The results showed that among the current injectors in the sample, 23 per cent reported 'any sharing' of syringes or needles, 45 per cent reported the sharing of 'any injecting paraphernalia' and 48 per cent reported the sharing of 'any injecting equipment overall' (Appendix Table 41a).…”
Section: Sharing Of Injecting Equipmentmentioning
confidence: 99%